ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Study pada perusahaan manufaktur yang terdaftar di BEI periode 2012-2013) - Lola Icha Shintya (AKT 15 UMY 400, 2015)
*400 This study was designed to analyze the effect of company size, profitability rate, solvency, the auditor's opinion and the profit/loss to the audit report lag operation. The objectif is manufacturing companies listed or listing on the Indonesian Stock Exchange (BEI) during 2012-2013. Sampling was done by purposive sampling technique. Data analysis was performed using multiple linear regression analysis. Data analysis was performed using multiple linear regression analysis. Prior to the first data analysis performed classical assumption that including normality test, multi-collinearity-test, autocorrelation test and testhetero-schedasdity